The Recruitment of Female “Mules” by Transnational Criminal Organizations: Securitization of Drug Trafficking in the Philippines and Beyond - Martel, Stéphanie (Archīum Ateneo, 2013)
Southeast Asia has long been vulnerable to drug trafficking. Recently, intensified flows of persons, goods, and capital across borders have rendered it more fragmented and complex. The recruitment of female drug “mules” by transnational criminal organizations is a growing concern for both national and international counter-trafficking authorities in the region. This phenomenon has been the focus of a particular securitization process, emerging primarily in the Philippines but having regional implications, which has supported the implementation of counter-trafficking policy initiatives on both levels of state and region in Southeast Asia.